PENERAPAN ALGORITMA LINEAR SEQUENTIAL SEARCH PADA APLIKASI KITAB FADHAIL AMAL BERBASIS MOBILE - Aprilia, Ryu; Hasibuan, Nelly Astuti; Ulfa, Kurnia (STMIK Budi Darma, 2017)
The development of mobile technology influences peoples lifestyles almost in every aspect of life. Utilization of mobile technology in the world of education also has an important role in adding alternative learning media such as applications that contain the content of substitute learning materials such as textbook books, dictionaries or books. The Book of Fadhail Charity contains the primacy of a deed based on the hadith of the Prophet. The discussion of the virtue of charity contained in the book of Fadhail Amal is quite extensive and deep enough that the size of the book is quite thick. The size of the book is quite thick it causes difficulty in finding a particular part of the book. For that required development of the Application containing the contents of the Book of Fadhail Charity where in the application there is a word search feature. Word search problems can be solved using string matching algorithms such as the LinearSequential Search algorithm. Linear Sequential Search can be used to solve text search problems with simple steps arranged in arrays. In this study designed a mobile-based applications that can run on androiZ smartphone, the application of charity-based fadhail book mobile will certainly be more portable and lightweight than the book fadhail heavy and very thick, Application of linear sequential search algorithms in fadhail book-based smartphone applications android will be very slavish users to find information contained in the book in addition to not heavy and also practical because it can be accessed anytime.